2008
DOI: 10.1007/s12149-007-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

FDG positron emission tomography imaging of drug-induced pneumonitis

Abstract: Several studies have reported the findings of fluorine-18-labeled fluoro-2-deoxy-D: -glucose positron emission tomography (FDG-PET) in benign lung disease with diffuse pulmonary injury; however, the characteristics and effectiveness of FDG-PET imaging for interstitial pneumonitis have not been substantiated. We report two cases of drug-induced pneumonitis in two patients treated for breast cancer who were diagnosed by FDG-PET examination. Both the cases showed diffuse interstitial infiltration in the bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Previous studies have demonstrated that a high everolimus trough concentration is associated with a higher risk of toxicity [14,28]. Increased FDG-avidity in the lungs on FDG-PET scans has been reported in several patients with drug-induced ILD such as bleomycin, rituximab, etoposide, and paclitaxel, mostly as diffuse bilateral FDG-accumulation [29][30][31][32][33][34][35]. FDG-PET has been reported to detect ILD earlier than high resolution computed tomography [36].…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Previous studies have demonstrated that a high everolimus trough concentration is associated with a higher risk of toxicity [14,28]. Increased FDG-avidity in the lungs on FDG-PET scans has been reported in several patients with drug-induced ILD such as bleomycin, rituximab, etoposide, and paclitaxel, mostly as diffuse bilateral FDG-accumulation [29][30][31][32][33][34][35]. FDG-PET has been reported to detect ILD earlier than high resolution computed tomography [36].…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…[ 18 F]-2-fluoro-2-deoxy-D-glucose positron emission tomography ( 18 F-FDG PET) is an imaging modality that detects the increased uptake of glucose in areas of increased cell metabolism. This technique is most often applied for diagnosis of malignancy, although it has also been found useful for detection of benign diseases [5], such as bronchiolitis obliterans organizing pneumonia (BOOP) [6], IPF [7], and drug-induced pneumonitis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Több esetet közöltek, amelyben a 18 FDG-PET/CT hasznos diagnosztikus eszköznek bizonyult a bleomycin indukálta tüdőkárosodás korai felismerésében [20,21]. A légzésfunkciós vizsgálatok és a konvencionális CTvizsgálat nem képes azonosítani a bleomycin indukálta gyulladás metabolikus aktivitását, viszont a 18 FDG-PET/ CT a metabolikus eltérések azonosítására is alkalmas, így lehetőséget teremt az aktív gyulladás és a residualis roncsolás megkülönböztetésére.…”
Section: Akut Károsodásunclassified